Effect of salicylic acid application in two basil cultivars submitted to water deficit - Carvalho, Josabete Salgueiro Bezerra de (2023)
Drought stress is one of the most limiting factors in the productivity of crops. Salicylic acid (SA) is a plant hormone that plays an important role in response to environmental stresses, including water deprivation stress.  Basil (Ocimum basilicum L.) is a water stress-sensitive plant and its cultivation can be strongly affected by prolonged periods of drought. Therefore, the objective of our work was to evaluate the possible attenuating role of AS in response to water stress in two basil cultivars. The experiment was conducted in the greenhouse of the Federal University of Agreste of Pernambuco. The experimental design was entirely randomized, with eight treatments: two varieties of basil (purple and green), two forms of AS application (with and without application), and two forms of irrigation (irrigated and without irrigation). The concentration of salicylic acid used was 2mM and its application was exogenous. As for the results, a reduction of 15.7% in the dry mass of the aboveground basil plants was observed when submitted to water deficit in irrigated plants. Significant differences were observed in the photosynthetic rate of the two basil varieties when exposed to AS. These results suggest that the use of AS at a concentration of 2mM contributed positively to the growth of both water-stressed and irrigated basil plants.